Development of E-Portfolio-Based Authentic Assessment of PNFI Learning Media Development Courses in the Out-of-school Education Study Program (PLS) Faculty of Teacher Training and Education (FKIP) Unpatti Ambon. - Lamberthus J. Lokollo (Peneliti.net, 2021)
The general objective of this research is to produce an e-portfolio-based authentic assessment model for the PNFI Learning Media Development course in the Foreign Education Study Program. School (PLS) Faculty of Teacher Training and Education, Pattimura University. The findings of this study indicate that developing an authentic portfolio-based assessment model has met all the criteria for an e-portfolio-based assessment model, and can be implemented as an assessment model in the PNFI Learning Media Development Course in the Out-of-school Education Study Program (PLS) Faculty of Teacher Training and Science. Education (FKIP) Unpatti Ambon